Assessing the effect of oxidative enzymes and stem anatomy on adventitious rooting of Olea europaea (L.) leafy cuttings - Denaxa, Nikoleta-Kleio; Roussos, Peter A.; Vemmos, Stavros N.; Fasseas, Konstantinos (Spanish Journal of Agricultural Research, 2019)
Aim of study: To assess the role of polyphenol oxidase (PPO), peroxidase (POD) and indole-3-acetic acid oxidase (IAAox) during adventitious rooting (Ar) in semi-hardwood cuttings of the easy-to-root olive cv. ‘Arbequina’ and the difficult-to-root cv. ‘Kalamata’. Simultaneously, a histological study was carried out in both cultivars to investigate the tissue related with Ar development. Area of study: The rooting experiments were carried out in ‘Kostelenos’ nurseries (Troizinia, Greece) and in Agricultural University of Athens. Material and methods: Plant material to set up the experiment was collected from current year shoots from 15-year-old mother plants of ‘Arbequina’ and ‘Kalamata’ at three different seasons (summer, autumn and spring). The auxin indole-3-butyric acid (IBA) at 2000 mg L-1 was used as rooting inducer. Main results: Analysis revealed that ‘Kalamata’ had significantly higher enzymatic activities before experiment onset and during Ar compared to ‘Arbequina’. Control cuttings of both cultivars exhibited increased enzymatic activities compared to IBA treated ones. IAAox was on average three times higher in ‘Kalamata’ than in ‘Arbequina’ and exhibited significant peaks during Ar. Similar peaks of POD and PPO activities were also detected. Histological analyses in ‘Kalamata’ revealed a continuous sheath of sclerenchyma ring and increased cortex thickness. Significant cell proliferation occurred in the phloem region in ‘Arbequina’ 15 days after planting and afterwards the root initials started developing in the secondary phloem from cambial cells. Research highlights: The differences in enzymatic activities as well as in stem anatomy could partly justify the different rooting ability of both cultivars.